Etiology of Emergency Visit and In-Hospital Outcomes of Patients with COPD - Xueyang Zhang; Qingtao Zhou; Shengfeng Wang; Qingbian Ma; Yongchang Sun (Emergency Medicine International)
Backgrounds. Patients with COPD often visit the emergency department (ED) due to exacerbation of respiratory symptoms (dyspnea, cough, and sputum production). Because manifestations of acute exacerbation of COPD (AECOPD) are nonspecific, differential diagnosis is critical in this acute setting. The causes for emergency visiting and the in-hospital outcomes are varied in patients with COPD. This study aimed to investigate the distributions of etiologies and the in-hospital outcomes of patients with COPD who presented to the ED because of exacerbation of respiratory symptoms. Methods. This was a retrospective study on COPD patients who had visited the ED and been hospitalized in a tertiary hospital because of worsening respiratory symptoms including cough, sputum production, and dyspnea from January 2017 to April 2020. Demographics, clinical manifestations, and laboratory studies in the ED were collected as the baseline data. The primary diagnosis at discharge or death was recorded. The hospitalization settings (general wards and ICU), the in-hospital outcomes, and associated factors were analyzed. Results. During the study period, 392 patients with COPD (male 302 (77.0%)), with a median age of 78 years, visited the ED and hospitalized in this hospital. The first 3 causes for emergency visit were AECOPD (n = 314, 80.1%), acute coronary artery syndrome with or without congestive heart failure (n = 24, 6.1%), and pulmonary embolism (n = 13, 3.3%). For patients with AECOPD (n = 314), 51.6% (n = 162) was admitted to ICU, and 6.4% (n = 20) died. Multivariate logistic analysis showed that age, atrial fibrillation, NT-pro BNP ≥300 pg/ml, and blood pH <7.3 were independent risk factors for ICU admission. Age, comorbid malignancy, NT-pro BNP ≥1800 pg/ml, and pneumonia on CT scan were independent risk factors for hospital mortality in patients with AECOPD. Conclusion. In COPD patients visiting the ED because of worsening respiratory symptoms, nearly 20% were due to non-AECOPD causes. For those with AECOPD, age, atrial fibrillation, NT-pro BNP ≥300 pg/ml, and blood pH <7.3 were independent risk factors for ICU admission, while advanced age, underlying malignancy, elevated NT-pro BNP, and pneumonia on CT scan were risk factors for hospital mortality.